Juvenile Idiopathic Arthritis With Epstein-Barr Virus-Associated Smooth Muscle Tumor in a 6-Year-Old Girl: A Rare Case Report - Kang, Zhijuan; Xu, Juan; Li, Zhihui (Frontiers in Pediatrics, 2021)
Herein, we reported a rare case of Epstein-Barr virus-associated smooth muscle tumor (EBV-SMT) combined with juvenile idiopathic arthritis (JIA) in a 6-year old patient without HIV/organ transplantation/congenital immunodeficiency. The patient suffered from pain in bilateral hip joints, which drastically affected her physical activity. Consequently, she was diagnosed with JIA (September 2019), after which she was given methotrexate and methylprednisolone pills via oral route, and a subcutaneous injection of recombinant human type Ⅱ tumor necrosis factor receptor-antibody fusion protein for four weeks that successfully relieved the pain. In May 2020, the pain reoccurred and was accompanied by occasional headaches. After extensive pathological examination, the patient was diagnosed with EBV-SMT. The imaging examinations after admission showed multiple lesions in the skull, lungs, and vertebral body. Biopsy of the L2 vertebral body was then performed to clarify the diagnosis, and finally, the in situ hybridization of the tumor of the lumbar vertebrae suggested non-HIV/transplantation-related EBV-SMT. Consequently, the patient received surgery without chemotherapy and radiotherapy, after which her conditions improved.